Desmontando a Sila: persuasión e intencionalidad histórica en la propaganda sobre el asedio de Atenas (87/6 aC) - Antela Bernárdez, Borja, 1977- (Historiae, 2014)
The account in the extant sources about the facts and circumstances related with the siege of Athens in 87/6 BC by L. Cornelius Sulla shows diverse curious links with the history of the glorious ancient past of Classical Athens. This kind of coincidences suggest to think not only in the possible propagandistic interest, maybe originated by Sulla himself, in relation with the appropiation of the memory of Athens, but also in the existence of a serie of mechanisms usuals in the elaboration of the historical works of the ancient authors at the light of the parametres that are not always directly related with the account of what really happened.